NUTRIENTS CONTENT OF THE BIOSUPPLEMENTS USING LIGNOCELLULOLYTIC BACTERIA BIOCATALYST - S. P., Ginting; Mudita, I M.; Cakra, I G. L. O. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the nutrients content of biosupplements using lignocellulolytic bacteria biocatalysts from the rumen fluid of bali cattle and termites. This research was conducted at the Sesetan Laboratory, Nutrition and Animal Feed Laboratory, Faculty of Animal Science, Udayana University. This research was conducted from June to September 2019. The design used was a completely randomized design (CRD) consisting of six treatments, namely biosupplement without lignocellulolytic bacteria (BS0) biocatalyst, biosupplement using Bacillus substilis BR4LG (BS1) biocatalyst, and biosupplement using Bacillus biocatalyst. substilis BR2CL (BS2), a biosupplement using the biocatalyst Aneurinibacillus sp. BT4LS (BS3), a biosupplement using Bacillus sp. BT3CL (BS4), and biosupplements using Bacillus sp. BT8XY (BS5). Each treatment had three replications. The variables observed were dry matter (%), organic matter (%), crude protein (%), crude fiber (%), crude fat (%), and ash (%). The results showed that quantitatively BS0 treatment had the highest percentage of organic matter (P>0.05) of 94.51% and the highest crude fiber content (P<0.05) of 5.71%. Quantitative BS2 treatment produced the highest percentage of ash (P>0.05) of 6.13% and the lowest percentage of crude fiber (P<0.05) of 3.06%. Quantitative BS4 treatment produced the highest percentage of dry matter (P>0.05) of 96.65% and produced the highest percentage of crude protein and crude fat (P<0.05) of 19.25% and 9.26%, respectively. . Based on the results of the study, it can be concluded that the use of lignocellulolytic bacterial biocatalysts can increase the nutrient content of biosupplements. The best bacterial biocatalyst in this study was Bacillus sp. BT3CL (BS4) produced the highest crude protein and crude fat content and Bacillus substilis BR2CL (BS2) produced the lowest crude fiber content.